Ethanol Extract of Detam 1 Soybean Seed (Glycine Max L. Merr) for Chronic Kidney Disease Therapy by In Vitro Study - Sijani Prahastuti; Meilinah Hidayat; Stella Tinia Hasiana; Wahyu Widowati; Annisa Amalia; Rismawati Laila Qodariah; Rizal Rizal; Satrio Haryo Benowo Wibowo; Hanna Sari Widya Kusuma (Majalah Obat Tradisional, 2019)
Chronic Kidney Disease (CKD) has increased incidence and prevalence in developing nations. In this in vitro study, we evaluated the cells proliferative effects, fibronectin (FN), transforming growth factor β (TGF-β1), and Reactive oxygen species (ROS) - level inhibition potential of ethanol extract of detam 1 soybean seed (EEDS) on glucose-induced kidney mesangial cells (SV40 MES 13). The cells proliferation assay used 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)2H-tetrazolium (MTS) assay. FN and TGF-β1 level were measured using ELISA assay kit and ROS level using flow cytometry. Level of   FN, TGF-β1 and ROS, on CKD cells model (5 mM, 10 mM glucose-induced mesangial cell) treated with EEDS 6.25 µg/mL were lower significantly compared to positive control,  EEDS improve cells viability and decrease FN, TGF-β1 and ROS level in glucose-induced kidney mesangial cells as CKD cells model.